1997
DOI: 10.1080/02652039709374511
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mycotoxins in raw ingredients used for animal feeding stuffs in the United Kingdom in 1992

Abstract: Examination of 330 samples of animal feed ingredients for the presence of a number of mycotoxins has been carried out. These samples were drawn from 186 animal feed mills in the United Kingdom. Aflatoxin B1 was the mycotoxin found most frequently, occurring in most samples of rice bran, maize products, palm kernels and cottonseed, but not in only 3 out of 20 samples of sunflower, in 1 out of 20 samples of soya and in no samples of peas, beans or manioc. Analytical difficulties were met with some combinations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 9 publications
2
48
0
1
Order By: Relevance
“…Disregarding the three highest values, the average value would change to 11.7 ng/g, which is much higher than the 2.5 ng/g average value measured by Trucksess et al (1999). In a survey of raw ingredients used for animal feedingstuffs, similar values were obtained by Scudamore et al (1997) who found OTA in 20% of the barley samples examined, with the highest value being 102 µg/kg.…”
Section: Ota Contamination Of Cereal Samplessupporting
confidence: 55%
See 1 more Smart Citation
“…Disregarding the three highest values, the average value would change to 11.7 ng/g, which is much higher than the 2.5 ng/g average value measured by Trucksess et al (1999). In a survey of raw ingredients used for animal feedingstuffs, similar values were obtained by Scudamore et al (1997) who found OTA in 20% of the barley samples examined, with the highest value being 102 µg/kg.…”
Section: Ota Contamination Of Cereal Samplessupporting
confidence: 55%
“…This mycotoxin is produced mainly by the mould fungi Aspergillus ochraceus and Penicillium verrucosum that grow on cereal grains and other plant-derived products during storage at 15-19% moisture content and temperatures exceeding 15 °C (Abramson et al, 1992). OTA contamination occurs in barley (Scudamore et al, 1997), wheat (Vrabcheva et al, 2000), maize (Scudamore and Patel, 2000) and other cereals (Jorgensen et al, 1996) with a prevalence and intensity that vary by year and by country. In Hungary, 14-15% of the feeds analysed in the 1970s was found to contain OTA (Sándor et al, 1982).…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%
“…On the other hand, contamination of animal feed ingredients with potentially harmful substances (e.g. mycotoxins) has been documented in both types of feedstuff (Scudamore et al, 1997), while neither organic nor conventional farm management can reduce the levels of persistent environmental pollutants, that may occasionally be found in feedstuffs and hence in endproducts of animal origin of both farming systems (Food and Agriculture Organization (FAO), 2000).…”
Section: Animal Feed Contaminants Disease Patterns and Veterinary Dmentioning
confidence: 99%
“…Scudamore and Hetmanski (1995) found STC in 8 (17 %) out of 46 samples of poorly stored cereals (wheat, barley and oats). In another study, Scudamore et al (1997) ). In three maize samples, co-occurrence of STC (between 7 and 574 µg/kg) with AFB 1 (between 24 and 503 µg/kg) and aflatoxin B 2 (AFB 2 ) (between 4.3 and 43 µg/kg) was observed (De Saeger, personal communication, 2012).…”
Section: Occurrence Of Sterigmatocystin In Grainsmentioning
confidence: 99%
“…Scudamore et al (1997) analysed 221 samples of feed ingredients (rice bran, maize gluten and products, cottonseed meal, rapeseed, sunflower meal, olive pulp, palm products, soya, peas/beans and manioc) using HPLC, but STC was not detected. Scudamore et al (1998b) tested 40 rice bran samples used in animal feed for the presence of 20 mycotoxins in the UK using HPLC (LOQ = 50 µg/kg).…”
Section: Occurrence Of Sterigmatocystin In Feedmentioning
confidence: 99%